The silicon isotopic composition of fine-grained river sediments and its relation to climate and lithology. (15th May 2018) - Bayon, G.; Delvigne, C.; Ponzevera, E.; Borges, A.V.; Darchambeau, F.; De Deckker, P.; Lambert, T.; Monin, L.; Toucanne, S.; André, L.
Abstract: The δ 30 Si stable isotopic composition of silicon in soils and fine-grained sediments can provide insights into weathering processes on continents, with important implications on the Si budget of modern and past oceans. To further constrain the factors controlling the distribution of Si isotopes in sediments, we have analysed a large number (n = 50) of separate size-fractions of sediments and suspended particulate materials collected near the mouth of rivers worldwide. This includes some of the world's largest rivers (e.g. Amazon, Congo, Mackenzie, Mississippi, Murray-Darling, Nile, Yangtze) and rivers from the case study areas of the Congo River Basin and Northern Ireland. Silt-size fractions exhibit a mean Si isotopic composition (δ 30 Si = −0.21 ± 0.19‰; 2 s.d.) similar to that previously inferred for the upper continental crust. In contrast, clay-size fractions display a much larger range of δ 30 Si values from −0.11‰ to −2.16‰, which yield a global δ 30 Siclay of −0.57 ± 0.60‰ (2 s.d.) representative of the mean composition of the average weathered continental crust. Overall, these new data show that the Si isotopic signature transported by river clays is controlled by the degree of chemical weathering, as inferred from strong relationships with Al/Si ratios. At a global scale, the clay-bound Si isotopic composition of the world's largest river systems demonstrates a link with climate, defining a general correlation with mean annual temperature (MAT) in corresponding drainage basins. While the distribution of Si isotopes in river sediments also appears to be influenced by the tectonic setting, lithological effects and sediment recycling from former sedimentary cycles, our results pave the way for their use as paleo-weathering and paleo-climate proxies in the sedimentary record.